Increased Mortality and Inflammation in Tumor Necrosis Factor-Stimulated Gene-14 Transgenic Mice after Ischemia and Reperfusion Injury - Souza, Danielle G. (American Society for Investigative Pathology, 2002)
TSG-14/PTX3 is a gene inducible by tumor necrosis factor (TNF)-α, interleukin-1β, and lipopolysaccharide in fibroblasts, macrophages, and endothelial cells. It encodes a 42-kd secreted glycoprotein that belongs to the pentraxin family of acute-phase proteins. Recently, we demonstrated that TSG-14 transgenic mice (TSG-14tg) overexpressing the murine TSG-14 gene under control of its own promoter are more resistant to lipopolysaccharide-induced shock and to polymicrobial sepsis caused by cecal ligation and puncture. Here we show that after ischemia and reperfusion (I/R) injury, TSG-14tg mice have an impaired survival rate, which appeared secondary to a markedly increased inflammatory response, as assessed by the local (duodenum and ileum) and remote (lung) enhancement in vascular permeability, hemorrhage, and neutrophil accumulation. Moreover, tissue concentrations of TNF-α, interleukin-1β, KC, and MCP-1 were higher in TSG-14tg as compared to wild-type mice after I/R injury. Of note, elevated TNF-α concentrations in serum were only observed in TSG-14tg mice and blockage of TNF-α action prevented lethality of TSG-14tg mice. These results demonstrate that transgenic expression of TSG-14 induces an enhanced local and systemic injury and TNF-α-dependent lethality after I/R. Taken together, our data point to a critical role of TSG-14 in controlling acute inflammatory response in part via the modulation of TNF-α expression.